Biomarkers of Cardiometabolic Risk, Inflammation and Disease - Palavra, Filipe; Reis, Flávio; Marado, Daniela; Sena, Armando (Springer International Publishing : Imprint: Springer, 2015)
This book discusses recent advances in the area of cardiometabolic risk biomarkers of chronic inflammatory and cardiovascular disorders. Tackling the topic in a systematic manner, the book starts with an introduction to cardiometabolic risk and its clinical relevance, comparing emergent and classical biomarkers. It then goes on to discuss cardiometabolic risk biomarkers in a range of diseases, including diabetes, ischemic stroke and neurodegenerative disorders.   Biomarkers of Cardiometabolic Risk, Inflammation and Disease is aimed at doctors specializing in internal medicine, neurology, cardiology, rheumatology, nephrology or endocrinology and will also be of interest to GPs, trainee doctors, and clinical and basic researchers working on cardiovascular and autoimmune disorders.